Aktivitas Antibakteri Minyak Biji Anggur terhadap Staphylococcus epidermidis dalam Sediaan Krim - Puspadewi, Ririn; Anggreani, Wulan; Faradilla, Agny Vardha (Pengurus Pusat Ikatan Apoteker Indonesia, 2025)
Grape seeds contain 75% unsaturated fats namely linoleic acid and vitamin E which contributes to its resistance to oxidation and is often chosen for use in the cosmetic, culinary, pharmaceutical, and health fields. The purpose of this study is to determine the activity of grape seed oil (Vitis vinifera L.) in inhibiting the growth of Staphylococcus epidermidis bacteria in cream preparations. The research was carried out through several stages, namely organoleptic examination of grape seed oil, making grape seed oil cream formula and its evaluation, testing antibacterial activity by disc diffusion method. Anti-acne cream preparations containing grape seed oil are made in 4 formulas, namely F0 (without grape seed oil), F1 (24%), F2 (30%), F3 (36%). All formulations during storage do not change shape, smell, and colour and homogeneity whereas pH and viscosity change during storage. The formulation of grape seed oil cream forms a stable cream from the results of freeze and thaw, showing no changes in globule size with globules <50μm. Based on the results of the antibacterial activity test, the best formula is F3, its provides the greatest inhibition against the growth of Staphylococcus epidermidis bacteria. Grape seed oil in cream preparations can inhibit the growth of Staphylococcus epidermidis.